The Key To Successful Character Education From Anies Rasyid Baswedan's Perspective - Rizky Firnanda; Mohamad Joko Susilo (PT. ALHAFI BERKAH INDONESIA, 2024)
This study aims to identify the keys to successful character education in the perspective of Anies Rasyid Baswedan by using the Systematic Literature Review (SLR) method. After a rigorous selection process based on inclusion criteria, including year of publication, indexation, and relevance to the topic, 26 articles were selected for analysis with a qualitative-descriptive approach. The results showed that the habituation of good values in daily life, inspirational leadership, and the role of a supportive environment are key elements in the success of character education according to Anies Rasyid Baswedan. The implementation of character education that focuses on the formation of moral character and performance is considered to be able to build a generation with integrity and resilience in facing global challenges.